Simulation of an Anti-Lock Braking System in a MATLAB/Simulink Environment for Various Road Adhesion Properties - KACPRZYCKI, Łukasz; BRUKALSKI, Mateusz; ABRAMOWSKI, Michał Mariusz; SAR, Hubert; FUNDOWICZ, Piotr (Engineering Transactions, 2025)
Driving safety is very important to every vehicle user. Automobile manufacturers compete by introducing increasingly advanced safety systems, which, when combined with appropriate driver response, help prevent road accidents. The demand for such systems in vehicles has been driven mainly by the dynamic development of automotive industry and continually increasing number of vehicles on the road. This paper deals with safety systems that monitor wheel longitudinal slip, with emphasis on testing an anti-lock braking system (ABS) in a MATLAB/Simulink environment. The aim of the work is to describe the development and operation of ABS, electronic stability program (ESP), acceleration slip regulation (ASR) and electronic brakeforce distribution (EBD) systems, and to develop a simulation model of ABS. The relationship between the tire-to-road adhesion coefficient and longitudinal wheel slip was modeled using the Magic Formula equation. The contribution of this system to the vehicle’s braking process on various surfaces (dry asphalt, wet asphalt, snow, and ice) and at various initial velocities was analyzed. In particular, braking distance as a function of time comparing scenarios with ABS activated and deactivated is presented. The structure of the paper includes a theoretical part overviewing automotive safety systems, a description of the ABS model, and an analysis of the results.